2018
DOI: 10.1021/acsaem.8b00213
|View full text |Cite
|
Sign up to set email alerts
|

Phase Directing Ability of an Ionic Liquid Solvent for the Synthesis of HER-Active Ni2P Nanocrystals

Abstract: An ionic liquid (IL) solvent was used to synthesize small, phase-pure nickel phosphide (Ni2P) nanocrystals. In contrast, under analogous reaction conditions, substitution of the IL for the common high-boiling organic solvent 1-octadecene (ODE) results in phase-impure nanocrystals. The 5 nm Ni2P nanocrystals prepared in IL were electrocatalytically active toward the hydrogen evolution reaction. The synthesis in IL was also extended to alloyed Ni2–x ­Co x P nanocrystals, where 0.5 ≤ x ≤ 1.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
5
24
0
Order By: Relevance
“…Many other earlier and later Ni 2 P preparations are available. 31,32,38,40,53,54,55 Without further modification, as made Ni 2 P nanocrystals have little catalytic activity. However, annealing under H 2 at 400 °C for 1 h greatly enhances the activity of Ni 2 P nanocrystals toward NO 3hydrogenation ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other earlier and later Ni 2 P preparations are available. 31,32,38,40,53,54,55 Without further modification, as made Ni 2 P nanocrystals have little catalytic activity. However, annealing under H 2 at 400 °C for 1 h greatly enhances the activity of Ni 2 P nanocrystals toward NO 3hydrogenation ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…77, 78 In all samples, the P 2p region also exhibits two peaks, a main one at 129.1 eV corresponding to phosphide (P 3-) in Ni 2 P, and another smaller peak at 133.2 eV characteristic of a fully oxidized phosphorous species (P 5+ ), most likely PO 4 3-. 53,56 Interestingly, both of the relative amounts of oxidized Ni (Ni 2+ ) and P (PO 4 3-) species on the Ni 2 P surface increase after annealing, and remain similarly high after catalysis ( Table 2). We explain these observations as follows: After initial synthesis, as made Ni 2 P nanocrystals contain small amounts of an NiO impurity on their surface.…”
Section: Resultsmentioning
confidence: 99%
“…TEM analysis of the Pt nanoparticles synthesized in ODE returns an average particle size of 1.7 ± 0.3 nm ( N = 300), and the nanoparticles were more agglomerated than what was observed for IL-synthesized particles (Figure S2). This can be attributed to the fact that ILs can stabilize colloidal nanoparticles (vide supra), , reducing agglomeration. Indeed, while the FT-IR spectra of Pt nanoparticles synthesized in ODE and IL both exhibit characteristic bands from PVP, the spectrum of the IL-synthesized particles also exhibits diagnostic bands for both the BMIM cation and the NTf 2 anion (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of work has explored ILs as alternative solvents for the fabrication of colloidal inorganic nanoparticles. When employed in nanoparticle synthesis, the low interfacial tension in ILs tends to facilitate rapid nucleation, while their high dielectric constant and ionic charge help to stabilize nanoparticles and support high colloid concentrations. Recent studies have shown that structured solvation layering of the ions in ILs at the nanoparticle surface prevents agglomeration and ultimately aids in colloidal stabilization of the particles. However, the main issue in adapting and ultimately scaling ILs lies in the high cost of these solvents, which can exceed $800/kg, making many industrial-scale applications untenable. To some extent, the high prices for IL solvents can be attributed to the relatively small scales at which these solvents are currently produced; however, unless and until larger IL production volumes yield lower prices, IL applications must prove their value in the context of high purchase costs.…”
Section: Introductionmentioning
confidence: 99%
“…Ordinarily, ILs are ionic salts that exist in the liquid state at room temperature, and are typically composed of organic N-containing heterocyclic cations and inorganic anions. ILs possess numerous merits, including reduced volatility, non-toxicity, a low vapor pressure, and high physico-chemical stability, which render them ideal candidates for the substitution of traditional volatile organic solvents and the sustainable synthesis of SMNCs [113][114][115][116]. It has been reported that the use of ILs as reaction media is highly efficient for the controllable synthesis of metal NPs of SMNCs, presenting several benefits [117][118][119][120]:…”
Section: Ionic Liquid-assisted Synthesismentioning
confidence: 99%